Wnt/B-catenin signaling pathway inhepatocellular carcinomas cases from Colombia (2015)
ABSTRACT: Background and aim. Hepatocellular carcinoma (HCC) is the most common primary liver cancer diagnosed worldwide. Deregulation of Wnt/β-catenin pathway has been associated with the development of HCC in a substantial number of cases in Europe and far less in Asia. Nothing is known about this pathway in HCC cases from South America. This study aimed to investigate the frequency of mutations in β-catenin gene (CTNNB1) and the subcellular localization of β-catenin in HCC cases from Colombia. Material and methods. We determine by direct sequencing the frequency of mutations in exon 3 of CTNNB1 gene and by immunohistochemistry the subcellular localization of β-catenin in 54 samples of HCC obtained from three pathology units in Bogota and Medellin cities. Results. Only three HCC cases (5.6%) were found mutated at residues (G34E, S45P, P44S, T41I) important for phosphorylation and ubiquitination of β-catenin protein. Strikingly, nuclear or cytoplasmic accumulation of β-catenin, hallmark of Wnt pathway activation, was found in 42.6% HCC cases (23/54). Interestingly, β-catenin accumulation was significantly more frequent in young patients and hepatitis B virus-related HCC. Conclusions. Although, CTNNB1 exon 3 mutations are not frequent in HCC from Colombian patients, our findings indicate that Wnt/β-catenin signaling is activated in 42.6% of HCC samples. Furthermore, Wnt signaling was demonstrated in HCC cases associated of HBV infection, one of the most important HCC risk factors in Colombia